Does Calculated Free Testosterone Overcome Total Testosterone in Protecting From Sexual Symptom Impairment? Findings of a Cross-Sectional Study. Issue 12 (1st December 2017) - Boeri, Luca; Capogrosso, Paolo; Ventimiglia, Eugenio; Cazzaniga, Walter; Pederzoli, Filippo; Moretti, Donatella; Dehò, Federico; Montanari, Emanuele; Montorsi, Francesco; Salonia, Andrea
Abstract: Background: Although erectile dysfunction (ED) has been associated with low circulating total testosterone (TT) levels, the utility of free testosterone (FT) over TT is debatable. Aim: To assess the relative impact of low TT and low calculated FT (cFT) on androgen-related sexual symptoms in men with ED. Methods: Data from 485 men were analyzed. Comorbidities were scored with the Charlson Comorbidity Index (CCI). Patients completed the International Index of Erectile Function (IIEF) and the Beck Inventory for Depression (BDI). Descriptive statistics tested differences between patients with normal TT levels (>3 ng/mL) and normal cFT levels (>65 pg/mL; group 1) and men with normal TT and low cFT (group 2), low TT and normal cFT (group 3), and low TT and low cFT (group 4). Linear regression models tested the association between clinical predictors and sexual function impairment. Outcomes: We assessed the impact of different hormonal categories on androgen-related symptoms and the clinical utility of measuring cFT in men with ED. Results: Groups 1, 2, 3, and 4 were composed of 338 (69.6%), 44 (9.1%), 34 (7.0%), and 69 (14.3%) patients, respectively. Compared with group 1, patients in group 2 were older ( P < .001), had a higher body mass index ( P  < .01), and had a larger proportion with CCI scores of at least 1 ( P  = .006). Likewise, group 2 presented lower scores for the IIEF erectile function ( P  = .07), sexual desire ( P  = .04), and orgasmic function ( P  = .007) domains and lower BDI scores ( P  = .02) than group 1. Similar findings were found for group 4 vs 1. Conversely, patients in group 3 had similar scores on the questionnaires to those in group 1. Low cFT and normal or low TT achieved independent predictor status for pathologic IIEF domains and BDI scores after accounting for age, CCI, and body mass index. Conversely, low TT and normal cFT status was not associated with pathologic scores on the questionnaires. Clinical Implications: The inclusion of cFT in the first-line assessment of hypogonadal symptoms in men with ED has major clinical utility. Strengths and Limitations: This is the first study evaluating the concomitant impact of TT and cFT on men with ED using well-validated instruments to assess patients' sexuality and depressive symptoms. Limitations are the retrospective nature of the study and lack of physical function data and bone ultrasound measurements. Conclusions: Although normal cFT was not associated with signs and symptoms suggestive of testosterone deficiency, even when concomitant with low TT or low cFT irrespective of TT values, it was indicative of poorer clinical profiles and impaired sexual and depressive parameters compared with normal TT and normal cFT in a cohort of patients with ED.